At-Risk Latin American Youth: Challenges to Change - Gibbons, Judith L. (2017)
Fostering the well-being of Latin American and Caribbean youth is vital to the region’s success. Despite their significant presence in the population, many youth face extraordinary challenges, such as poverty, exposure to violence, and lack of access to quality education. We review some successful interventions from an ecological perspective that address the needs of at-risk youth in the region. Interventions in a variety of countries have been aimed at altering the microsystems or ecosystems of youth as well as involving them directly. Direct interventions with youth must involve them in meaningful activities that provide a sense of empowerment. The lessons learned from these interventions reveal the outstanding potential of youth to thrive despite the obstacles they face.